2012
DOI: 10.1177/0091270011421911
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic and Pharmacodynamic Model‐Based Comparability Assessment of a Recombinant Human Epoetin Alfa and the Biosimilar HX575

Abstract: The aim of this study was to develop an integrated pharmacokinetic and pharmacodynamic (PK/PD) model and assess the comparability between epoetin alfa HEXAL/Binocrit (HX575) and a comparator epoetin alfa by a model-based approach. PK/PD data—including serum drug concentrations, reticulocyte counts, red blood cells, and hemoglobin levels—were obtained from 2 clinical studies. In sum, 149 healthy men received multiple intravenous or subcutaneous doses of HX575 (100 IU/kg) and the comparator 3 times a week for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 69 publications
(130 reference statements)
5
41
0
Order By: Relevance
“…Sotatercept administration resulted in a rapid onset of its erythropoietic effects in a dose‐dependent manner at the three dose levels tested. These kinetics suggests that sotatercept may be at least partly targeting late‐stage RBC precursors downstream of the early stage proliferative effects of ESAs . Furthermore, as more mature erythroblasts are released into circulation, a feedback mechanism is potentially activated to supply early progenitors by increasing EPO concentration, which might explain the paradoxical delayed increase in EPO after 1 month in the presence of an increase in hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Sotatercept administration resulted in a rapid onset of its erythropoietic effects in a dose‐dependent manner at the three dose levels tested. These kinetics suggests that sotatercept may be at least partly targeting late‐stage RBC precursors downstream of the early stage proliferative effects of ESAs . Furthermore, as more mature erythroblasts are released into circulation, a feedback mechanism is potentially activated to supply early progenitors by increasing EPO concentration, which might explain the paradoxical delayed increase in EPO after 1 month in the presence of an increase in hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Population PK/PD modeling offers insight into potential differences between the biosimilar and originator at a mechanistic level and can incorporate nonstationary and nonlinear PK/PD that might otherwise be confounding using standard (e.g., NCA) approaches. It has been applied recently within the EMA for an epoetin biosimilar as evidence for PK/PD comparability . Here, the authors found similar results to the classic NCA approach, but noted limitations in the model‐based approach due to the complexity of the model and a mismatch between the data collected in the clinical studies and the data needed to parameterize such a model.…”
Section: Exposure–response Relationships: Demonstrating Clinical Compmentioning
confidence: 58%
“…In the context of a biosimilar, this approach can be used to detect differences between originator and biosimilar, provided there is enough power and the strength and limitations of the model‐based analysis are well understood. This approach is similar to that used in model‐based bioequivalence testing, where the confidence interval of the ratio of the originator and biosimilar parameter estimates (e.g., EC 50 , the drug concentration of half‐maximal effect) is compared with a prespecified acceptance range and can provide valuable supporting information to the standard analysis of the biosimilarity . The criteria and methodology for declaring comparable efficacy on exposure–response parameters should be predefined, and the variability in exposure–response for the originator can inform this criteria.…”
Section: Exposure–response Relationships: Demonstrating Clinical Compmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initially generated based on the behavior observed in a number of small‐molecule compounds mentioned above, the concept of TMDD is more widely recognized and well appreciated in peptide‐ and protein‐based pharmaceuticals (ie, large‐molecule compounds) due to the high prevalence of TMDD in this type of drug. Numerous large‐molecule compounds, including interferon‐β1a, erythropoietin, thrombopoietin, M‐CSF, pegfilgastim, and various monoclonal antibodies, have been reported to exhibit nonlinear pharmacokinetics imparted by TMDD . Different from large‐molecule compounds, which usually have high‐affinity binding to their pharmacological targets with minimal nonspecific tissue binding, the saturable target binding of small‐molecule compounds is often masked by the binding to those nonspecific sites (tissue and/or plasma) whose capacity is usually larger.…”
mentioning
confidence: 99%